Students with Fetal Alcohol Syndrome Participating in Recess - Scheel, Rebecca; Lucas, Matthew D. (Journal of the American Academy of Special Education Professionals, 2011)
For the student with Fetal Alcohol Syndrome (FAS), participation in recess can often be both challenging and rewarding for the student and teacher. This paper will address common characteristics of students with FAS and present basic solutions to improve the experience of these students in the recess setting. Initially, the definition and prevalence of FAS will be presented. This will be followed by a discussion of the benefits of the recess setting for the student. Next, as a lead-up to the specific topic of recess for students with FAS, a discussion of possible modifications and teaching strategies for working with children with FAS in the classroom will be noted. The paper will then address the possible challenges and subsequent modifications and teaching strategies for working with children with FAS in recess. Lastly, specific methods of proactively including a student with FAS in a recess activity will be discussed.